WORKSHOP IMPLEMENTASI KURIKULUM MARDEKA PENYUSUNAN PERANGKAT PEMBELAJARAN & PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) UNTUK GURU GURU SMKS & SMAS YPK MEDAN - Darmawati Darmawati (Jurnal Pengabdian Mitra Masyarakat, 2023)
The Mardeka curriculum is motivated by the results of the Program for International Student Assessment (PISA) which shows that 70% of students aged 15 years are below the minimum competence in understanding simple reading or applying basic mathematical concepts. This PISA score has not experienced a significant increase in the last 10-15 years. In addition, there are large disparities between regions and between socio-economic groups in terms of the quality of learning which has been exacerbated by the COVID-19 pandemic. Educators and education practitioners around the world are starting to realize that learning things outside the classroom can help students develop better. Studying things in everyday life can increase students' sensitivity and concern for the surrounding environment. However, in practice this has not been done optimally in the current education system. The Mardeka Curriculum Implementation Workshop for the Preparation of Learning Devices the Project to Strengthen Pancasila Student Profiles (P5) for SMKS and SMAS YPK Medan teachers was held for 4 days. During the workshop, there were 107 participants who attended. As a percentage, the total attendance of participants was 95%.